Biomechanical characterization of the small intestine to simulate gastrointestinal tract chyme propulsion. (24th March 2022) - Carvalho, Mariana R.; Ferreira, João P. S.; Oliveira, Dulce A.; Parente, Marco P. L.; Natal Jorge, Renato M.
Abstract: Regular intestinal motility is essential to guarantee complete digestive function. The coordinative action and integrity of the smooth muscle layers in the small intestine's wall are critical for mixing and propelling the luminal content. However, some patients present gastrointestinal limitations which may negatively impact the normal motility of the intestine. These patients have altered mechanical and muscle properties that likely impact chyme propulsion and may pose a daily scenario for long‐term complications. To better understand how mechanics affect chyme propulsion, the propulsive capability of the small intestine was examined during a peristaltic wave along the distal direction of the tract. It was assumed that such a wave works as an activation signal, inducing peristaltic contractions in a transversely isotropic hyperelastic model. In this work, the effect on the propulsion mechanics, from an impairment on the muscle contractile ability, typical from patients with systemic sclerosis, and the presence of sores resultant from ulcers was evaluated. The passive properties of the constitutive model were obtained from uniaxial tensile tests from a porcine small intestine, along with both longitudinal and circumferential directions. Our experiments show decreased stiffness in the circumferential direction. Our simulations show decreased propulsion forces in patients in systemic sclerosis and ulcer patients. As these patients may likely need medical intervention, establishing action concerning the impaired propulsion can help to ease the evaluation and treatment of future complications. Abstract : Chyme propulsion during peristalsis in the small intestine is numerically investigated, both axially and in impaired patients. The small intestine is modeled as a transversely isotropic hyperelastic material with passive and active behavior and chyme as a rigid body. The mechanical properties of the duodenum and ileum are obtained with uniaxial tensile tests in the longitudinal and transverse directions. Experimental results show directional and axial variation in passive response, whereas numerical results reveal decreased propulsion in patients with systemic sclerosis and ulcers.